Strength Analysis of an Aircraft Sandwich Structure with a Honeycomb Core: Theoretical and Experimental Approaches - Sadiq E. Sadiq; Muhsin J. Jweeg; Sadeq H. Bakhy (Engineering and Technology Journal, 2021)
In this paper, the strength of aircraft sandwich structure with honeycombcore under bending load was evaluated theoretically and experimentallybased on failure mode maps. A failure mode map for the loading underthree-point bending was constructed theoretically to specify the failuremodes and corresponding load. Three point bending test for aluminumhoneycomb sandwich beam has been achieved to measure the peak loadand maximum deflection. The obtained results elucidated a goodagreement between the theoretical solutions and experimental tests, wherethe error ratio was not exceeded 12%. The core height, the cell size andthe cell wall thickness were selected to explore the effect of honeycombparameters on the strength of sandwich structure. In order to obtain theoptimum solution of peak load and maximum deflection and energyabsorption, Response Surface Methodology (RSM) was used. Resultsshowed that the maximum bending load, minimum deflection, andmaximum energy absorption were found at 25 mm core height, 10 mm sizecell and 1 mm cell wall thickness. The optimal value of maximum bendingload, minimum deflection and maximum energy absorption were1975.3415 N, 1.0402 mm and 1.0229 J respectively.